Subacute Cutaneous Lupus Erythematosus-Like Eruption Induced by Durvalumab: A Case Report and Literature Review - Pratumchart N; Chanprapaph K; Topibulpong N; Tankunakorn J (Dove Medical Press, 2022)
Nathathai Pratumchart,1 Kumutnart Chanprapaph,1 Nuttapong Topibulpong,2 Jutamas Tankunakorn1 1Division of Dermatology, Department of Internal Medicine, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, Bangkok, Thailand; 2Division of Oncology, Department of Internal Medicine, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, Bangkok, ThailandCorrespondence: Jutamas TankunakornDivision of Dermatology, Faculty of Internal Medicine, Ramathibodi Hospital, Mahidol University, Bangkok, 10400, ThailandTel +66 22011141Fax: +66 22011211Email Tankunakorn@gmail.comAbstract: Reports of immune-related adverse events caused by programmed cell death-ligand 1 (PD-L1) inhibitor have been emerging. Herein, we report a subacute cutaneous lupus erythematosus (SCLE)-like eruption presented after the treatment of durvalumab in a patient with extensive-stage small cell lung carcinoma. A 74-year-old Thai man was referred to our department after experiencing multiple dusky red to brownish papules and patches with scale and erosions on photo-distributed areas after receiving 3 infusion cycles of durvalumab. Histological finding revealed epidermal atrophy with interface changes and superficial perivascular infiltration of lymphocytes. Serum antinuclear antibodies (ANA) was 1:320 and anti-Ro/Sjogren’s-syndrome-related antigen A (anti-Ro/SSA) antibodies were positive (2+). Based on the history and clinicopathological correlation, the diagnosis of SCLE-like eruption due to durvalumab was made. To the best of our knowledge, this is the first case of durvalumab-induced SCLE.Keywords: programmed cell death-ligand 1 inhibitor, durvalumab, subacute cutaneous lupus erythematosus, immune-related adverse events